A study on raise blasting and blast-induced vibrations in highly stressed rock masses. (May 2022) - Huo, Xiaofeng; Shi, Xiuzhi; Qiu, Xianyang; Zhou, Jian; Gou, Yonggang; Yu, Zhi; Zhang, Shian
Highlights: An effective raise blast technique with vertically parallel and dense bunch holes. An accurate numerical model for raise blasting under in-situ stress. In-situ stress governs the radial cracks but has little effect on the crush zone. In-situ stress can reduce PPA and frequency of the blast-induced vibration. Short-delay blast can effectively reduce the cut blasting induced vibration. Abstract: In deep underground mining, the damage evolution and vibration response mechanisms of rock caused by cut blasting are different from those of shallow rock. It is essential to understand the mechanisms for underground engineering safety. In this study, field raise blasting with vertically parallel and dense bunch longholes was designed and performed at the Shaxi underground mine in China. The raise contour and the blasting vibration were measured in the field, and regression analyses of the peak particle acceleration (PPA) were performed. Then, a numerical model considering the effect of in situ stress was developed and calibrated to simulate raise blasting excavation. The damage contours show that the in-situ stress can reduce the radial fractures outside the raise, but has little influence on the crater. The vibration analyses indicate that the PPA and the average frequency (AF) decrease with an increasing in-situ stress. The confinement effect of in-situ stress on vibration characteristics is discussed, and blast loading relative pressure curves are presented for a demonstration. It is determined that the relative pressure peak value decreases, and the rising time and duration time increase with an increasing the in-situ stress; as a result, the blast-induced vibration is lower in amplitude and AF. In terms of the frequency, the vibration from a higher in-situ stress is more harmful to structures. A short-delay blasting model was conducted, and the results show that it can effectively reduce the structural vibration damage caused by cut blasting.